CONTINUING EDUCATION FOR TEACHERS IN YOUTH AND ADULT EDUCATION: CHALLENGES AND PROPOSITIONS FOR TEACHING PRACTICE (Interdisciplinary Studies Journal, 2023)
We’re presenting the results of the university extension project entitled: Continuing training of Youth and Adult Education Teachers: Challenges and Propositions for Teaching Practice developed throughout the year 2020 at the Faculdade de Filosofia Dom Aureliano Matos/ FAFIDAM/ UECE. In terms of methodology, this project is qualitative assuming the characteristic of the experience report, because we present the steps taken by this project, relying on authors such as Freire (1987, 1996), Nunes; Carvalho e Mendes (2014), Silveira; Oliveira e Feitosa (2020) and Oliveira; Costa and Holanda (2021). As a result of the research, we identified that the modality of EJA needs better support in the scope of training initial and continuing education, methodologies, accessibility, and appreciation of the work of teachers.
Keywords: Youth and Adult Education; Continuing education; challenges of teaching practice; University Extension